Loss and Dysregulation of Th17 Cells during HIV Infection - Sandra L. Bixler; Joseph J. Mattapallil (Clinical and Developmental Immunology)
Bacterial translocation across the damaged mucosal epithelium has emerged as a major paradigm for chronic immune activation observed during HIV infection. T helper 17 (Th17) cells are a unique lineage of T helper cells that are enriched in mucosal tissues and are thought to play a central role in protecting the integrity of the mucosal barrier and maintaining immune homeostasis at mucosal sites. Th17 cells are lost very early during the course of HIV infection, and their loss has been shown to correlate with bacterial translocation. Interestingly, Th17 cells are unable to completely recover from the early destruction even after successful antiretroviral therapy (ART). Here, we review some of the potential mechanisms for the loss and dysregulation of Th17 cells during HIV infection.